Development of low glycaemic carrot cake by partially substituting sugar with concentrated nypa fruticans sap - Yee, Tai Yen (2020)
Nypa fruticans sap (NFS) or neera juice is a traditional sugar-rich palm sap beverage consumed among the Malay community in Malaysia. Being a natural sweetener, NFS could potentially be used as novel source to replace added sugar in bakery product. This study aimed to develop carrot cakes incorporated with concentrated N. fruticans sap (CNFS) and to determine the effects of nutritional compositions, textural profile, antioxidant capacity, sensorial acceptability and glycaemic index (GI) values. Fresh NFS was dehydrated into concentrated form and added in carrot cake formulations as partial replacement (0, 5, 10, 15 and 20%) for table sugar. Results indicated that incorporation of CNFS at 20% level significantly (p<0.05) increased the nutritional compositions of carrot cakes which recorded the highest moisture (33.31%), ash (1.47%) and dietary fiber (10.75%) content. In texture profile analysis, a slight decrease in hardness, springiness and resilience were reported with increasing levels of CNFS substitution in carrot cakes. For antioxidative activities, 20% CNFS-incorporated carrot cake methanol extract showed the highest total phenolic content (TPC), free radical scavenging effect on the 2,2-diphenyl-1- picrylhydrazyl (DPPH) and reducing power (RP) in comparison to control and other carrot cake methanol extract. Sensory acceptability test revealed that carrot cake formulated with 20% CNFS received better acceptability score for appearance, texture, taste and flavour compared to carrot cake without NFS. Based on sensorial acceptability results, two formulations of carrot cakes (0 and 20% CNFS) wereselected for GI testing. It was found that the GI of carrot cake with 20% CNFS was 50 while the 0% CNFS carrot cake was 55. Although CNFS did not significantly lower the postprandial peak glucose responses, it can significantly lower the GI value of carrot cake. The results of this study showed that carrot cake incorporated with 20% CNFS could be an effective way to develop low GI cake with desirable physical and sensorial acceptability.